Microencapsulação de Bifidobacterium lactis e Lactobacillus acidophilus por coacervação complexa: estudo da produção, caracterização e viabilidade - Silva, Thaiane Marques da (2016)
Probiotic cultures have been used in food because of its beneficial effects on human health. However, the viability of the probiotic bacteria in food is often low because these microorganisms do not survive during storage of the product due to various adverse factors. Accordingly, the microencapsulation is an alternative. Microencapsulation is the protection of a compound and modulation of its release and now, several techniques are available, highlighting the complex coacervation. The complex coacervation technique has some advantages over other techniques such as the possibility of working with biopolymers, the absence of organic solvent and temperature conditions in mild processing. The objective of this study was to apply the complex coacervation technique to encapsulate B. lactis and L. acidophilus using gelatin and gum arabic as coating materials and perform the drying of the microcapsules by lyophilization. Moreover, it was analyzed zeta potential of the coating material for the production of microcapsules, the microcapsules morphology by light microscopy and scanning electron microscopy, and the average diameter and the encapsulation efficiency. The microcapsules were evaluated in the wet and dry forms, also considering the resistance of microorganisms to the drying process by lyophilization, storage at room temperature (25°C), cooled (7°C) and freezing (-18°C) for 120 days. Resistance was evaluated "in vitro" when inoculated in buffer solutions of different pH and front of the simulated human gastrointestinal tract. It was found that for both micro encapsulation by complex coacervation is effective in forming uniform probiotic microcapsules with mean diameters suitable to the process and with high encapsulation efficiency. It was also observed that probiotics were resistant to drying by lyophilization process, showing viability (> 6logUFC.g-1). The resistance to storage at different temperatures was also observed with the temperature being -18°C, the most efficient in protection of probiotics. Additionally, the microcapsules were effective to protect the probiotics against the different conditions of pH and simulated gastrointestinal conditions. Finally, the encapsulation by complex coacervation process was adequate, providing protection, controlled release and resistance to various adverse conditions, such as pH, temperature and gastrointestinal tract, and presents a number of advantages compared to other techniques.